Influence of variety and season in the inflorescence sap production in Cocos nucifera L. - Samsudeen, K.; Niral, V.; Jerard, B.A.; Kumar, Mukesh; Sugatha, P.; Hebbar, K.B. (Journal of Plantation Crops, 2013)
The unfermented inflorescence sap of coconut is nutritionally rich and is being popularized as a natural health drink. The present work was initiated to understand the influence of variety and season on the inflorescence sap production and its quality in selected varieties of coconut. Three varieties of coconut viz., West Coast tall (WCT), Laccadive Ordinary Tall (LCT) and Chawghat Orange Dwarf (COD) and one hybrid CODxWCT (Chandra Sankara) grown at CPCRI, Kasaragod were selected for the study during 2010 and 2011. The work was undertaken for four seasons viz., monsoon, post monsoon, winter and summer. The study revealed that tall varieties are better than dwarf varieties for sap production. Average sap production of 960 ml and 880 ml respectively, in WCT and DxT hybrids was the best among the varieties tested. Sap production in COD was very low and not suitable for tapping. Total sugar content in WCT (11.44 g 100 ml–1) was the highest among the varieties tested. DxT had high reducing sugar content (0.37 g 100 ml–1). The study also revealed that the best time for tapping is from the middle of monsoon to the beginning of winter season. Tapping should be avoided during summer months under rainfed conditions. The information generated is useful to the farmers for tapping of coconut palm by regulating the time of tapping, identifying suitable varieties and providing irrigation to increase sap production.